Kompetensi Digital Guru SMK Menghadapi Tantangan Pembelajaran Digital - Masnah, Siti Laily; Komaro, Mumu; Sumardi, Kamin (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to obtain digital competency data for vocational school teachers, digital training that has been attended by vocational teachers, the use of digital infrastructure, and the readiness of schools to face digitalization. The research method used is ex-post facto through a survey with a quantitative descriptive approach. The survey was conducted on 39 teachers at SMKN 8 Bandung. Data is collected through a questionnaire using the Google form. The results of the study showed that the digital competency of vocational school teachers was quite good. On average, 67% of vocational teachers already have digital competence. Teachers who have attended training related to digital competence obtained data of 32%. All teachers have utilized digital infrastructure in schools, but this has not been done optimally. A small number of teachers still experience difficulties in utilizing digital learning infrastructure. School readiness in preparing for digitalization of learning obtained data of 76%. These results show that the digital competency of vocational school teachers and school readiness in facing digitalization must be improved.